THE QUEST FOR RIGHTS OF POLYAMOROUS FAMILY UNIONS (REMUNOM, 2023)
The article addresses the evolution of family groups, emphasizing their nature not only as a biological entity but also as a social phenomenon, according to Durkheim's perspective. The 1988 Federal Constitution does not rigidly define the family entity, allowing for a broad interpretation. Authors such as Maria Berenice Dias, Flávio Tartuce, and Paulo Lôbo highlight the need for recognition of various family formations beyond the traditional model. The text questions whether the legal concept of family should encompass other configurations beyond those composed of two individuals, considering the adaptation of Family Law to social diversity. The expansion of rights in cases such as divorce, adoptive children, same-sex families, and multiparentality is discussed. It is highlighted the lack of legal recognition for families united in polyamory, despite records of polyfidelitous unions between 2012 and 2016. The National Council of Justice (CNJ) prohibited the registration of these unions in 2018, based on the justification provided by Minister João Otávio de Noronha, citing the lack of social acceptance, absence of judicial action, and insufficient maturity regarding the implications of polyamorous relationships. The article aims to critically analyze these justifications, using sources such as news articles, documents, academic research, and doctrinal positions. The analysis will cover state protection of the family, the right of families from the perspective of Constitutionalized Civil Law, and its relationship with families in polyamorous unions.